Full-length haplotype reconstruction to infer the structure of heterogeneous virus populations. Issue 14 (27th June 2014) - Giallonardo, Francesca Di; Töpfer, Armin; Rey, Melanie; Prabhakaran, Sandhya; Duport, Yannick; Leemann, Christine; Schmutz, Stefan; Campbell, Nottania K.; Joos, Beda; Lecca, Maria Rita; Patrignani, Andrea; Däumer, Martin; et al.
Abstract: Next-generation sequencing (NGS) technologies enable new insights into the diversity of virus populations within their hosts. Diversity estimation is currently restricted to single-nucleotide variants or to local fragments of no more than a few hundred nucleotides defined by the length of sequence reads. To study complex heterogeneous virus populations comprehensively, novel methods are required that allow for complete reconstruction of the individual viral haplotypes. Here, we show that assembly of whole viral genomes of ∼8600 nucleotides length is feasible from mixtures of heterogeneous HIV-1 strains derived from defined combinations of cloned virus strains and from clinical samples of an HIV-1 superinfected individual. Haplotype reconstruction was achieved using optimized experimental protocols and computational methods for amplification, sequencing and assembly. We comparatively assessed the performance of the three NGS platforms 454 Life Sciences/Roche, Illumina and Pacific Biosciences for this task. Our results prove and delineate the feasibility of NGS-based full-length viral haplotype reconstruction and provide new tools for studying evolution and pathogenesis of viruses.